2019
DOI: 10.2147/ijwh.s160022
|View full text |Cite
|
Sign up to set email alerts
|

<p>Severe maternal morbidity (near-miss) and its correlates in the world&rsquo;s newest nation: South Sudan</p>

Abstract: BackgroundThis study investigates the frequency of near-miss events and compares correlates in the world’s newest nation.MethodsA cross-sectional study was carried out to audit near-miss events and their causes. A total of 1,041 mothers were sampled. Data were gathered using World Health Organization near-miss evaluation tools according to morbidity and organ failure-based criteria. Intensive care unit admission criteria were not used (as there is no functional intensive care unit in Juba Teaching Hospital). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 25 publications
(44 reference statements)
4
17
1
5
Order By: Relevance
“…This study showed that women who had initially diagnosed with pregnancy-induced hypertension were 5.3 times more likely to develop maternal near-miss than those without pregnancy-induced hypertension. This is consistent with the study done in Kathmandu Hospital [24]; Tigray, Ethiopia [12]; Sudan [21]; and southeast Iran [8].This might be a reflection of poor management of pregnancy-induced hypertension cases in the peripheral health centers as 50.8% of them were referral cases. On the other hand, this might be due to delay in seeking appropriate treatment because of lack of proper referral system and early detection of lifethreatening conditions like eclampsia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study showed that women who had initially diagnosed with pregnancy-induced hypertension were 5.3 times more likely to develop maternal near-miss than those without pregnancy-induced hypertension. This is consistent with the study done in Kathmandu Hospital [24]; Tigray, Ethiopia [12]; Sudan [21]; and southeast Iran [8].This might be a reflection of poor management of pregnancy-induced hypertension cases in the peripheral health centers as 50.8% of them were referral cases. On the other hand, this might be due to delay in seeking appropriate treatment because of lack of proper referral system and early detection of lifethreatening conditions like eclampsia.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the last reason might be that, because of the limited facilities at the private hospitals, women with complicated pregnancies are not usually referred to these health institutions. In contrast, this study is lower as compared with the studies conducted in South Sudan 94.1% [21], Northeast Region of Brazil 31.5% [22], Southeast Iran 25.2% [8], Brazilian demographic health survey 21.1% [23], and Debre-Markos hospital, Ethiopia, 29.7% [23]. The primary possible explanation might be due to the small sample size and short study period in the current study.…”
Section: Discussioncontrasting
confidence: 68%
“…This is contrary with the finding of the study conducted in which states that mothers with higher parity and gravidity were important predictors for the occurrence of maternal near miss events. 17,21,37 This might be partly explained by the fact that women who experienced prior peaceful labor at home delivery might believe that things go similarly every time in pregnancy and might decide to give birth at home.…”
Section: Discussionmentioning
confidence: 99%
“…A multi-country study conducted in LMIC reported that closing the quality gap would produce substantial bene ts in maternal and neonatal health at current levels of access and utilization of healthcare services [8]. Therefore, reducing maternal mortality and morbidity in Cameroon hinges on identifying and improving services that are critical to the health of women and girls, such as; Antenatal Care, Emergency Obstetric and New-born Care (EmONC), skilled birth attendance and quality healthcare before, during and after childbirth [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%